Click to Care: The Role of Digital Credibility and E-brand Image in Medical Tourism Decision-making - T, Divya; Sridar, K Karthik (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
This study aims to examine how digital factors influence medical tourists’ decision-making intention in the context of cross-border healthcare. Specifically, it investigates the impact of online review credibility, information transparency in online platforms, and e-brand image on hospital selection decisions in medical tourism. A quantitative, cross-sectional survey design was adopted. Data were collected through a structured questionnaire using a five-point Likert scale from individuals who actively use online platforms for healthcare information and medical travel decisions. A total of 221 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test reliability, validity, and hypothesized relationships among constructs. The results reveal that all three digital variables have a positive and significant effect on medical tourist decision-making intention. Among them, e-brand image emerged as the strongest predictor, followed by information transparency and online review credibility. The model demonstrated high explanatory power, indicating that digital cues substantially shape behavioral intentions in medical tourism. This study offers an integrated empirical framework that combines digital marketing constructs with medical tourism decision behavior, addressing a gap where prior studies examined these elements separately rather than collectively. The study is limited to cross-sectional data and self-reported perceptions, which may restrict long-term generalizability and behavioral prediction.
Keywords: Medical Tourism; Online Review; Information Transparency; E-Brand Image; Decision-Making Intention; Digital Healthcare; word of mouth